PENGARUH STRUKTUR ASSET DAN PERTUMBUHAN PENJUALAN TERHADAP KEBIJAKAN UTANG - Yati Mulyati (UPT Penerbitan Universitas Jember)
This study aimed to examine the effect of Structure Asset and sales growth against debt policy on food and beverages companies listed on the Stock Exchange in 2010-2014. Variable Structure Asset measured by the proportion of total assets and total assets in the form of a percentage. Variable sales growth was measured by comparing the sales in the current year (t) net of sales of the previous period (t-1) to sales in the previous period (t-1) multiplied by 100%. Debt policy variables proxied by dividing total debt by total equity (DER). Data analysis method used is descriptive analysis method and analysis methods verification. Selection of the samples in this study using purposive sampling method. Samples were selected in this study were six food and beverages company listed on the Stock Exchange in 2010-2014. The analytical tool used is multiple regression analysis. Based on the hypothesis testing showed that the structure of Asset no significant effect on the debt policy. Sales growth significantly influence debt policy.